Microstructure and mechanical properties of composite cements: reactivity of pozzolanic and hydraulic cementitious materials - Gómez-Zamorano, L. Y.; Iñiguez-Sánchez, C. A.; Lothenbach, B. (Revista ALCONPAT, 2015)
This research was focused on the use of pozzolanic and hydraulic additions as partial replacement ofPortland cement. In order to evaluate the mechanical properties, microstructure and hydration reactions ofthe composite cements phases, granulated blast furnace slag, fly ash, metakaolin, and geothermal silicawere used as replacement materials. The following conditions were utilized: replacement levels of 50, 40and 30% of the mentioned materials, a water/cementitious materials ratio of 0.4, curing temperatures of 20and 50°C and curing intervals from 3 to 180 days. The results indicated a high degree of reactivity ofreplacement materials and an increase in the mechanical properties up to 200% compared to pure cement,resulting in a matrix of more dense reaction products and thus a reduction in porosity.Keywords: Microstructure, reactivity, mechanical properties, industrial byproducts.